Within-subjects comparison of the HiRes and Fidelity120 speech processing strategies: Speech perception and its relation to place-pitch sensitivity - Donaldson, Gail S. (2011)
OBJECTIVES: Previous studies have confirmed that current steering can increase the number of discriminable pitches available to many CI users; however, the ability to perceive additional pitches has not been linked to improved speech perception. The primary goals of this study were to determine (1) whether adult CI users can achieve higher levels of spectral-cue transmission with a speech processing strategy that implements current steering (Fidelity120) than with a predecessor strategy (HiRes) and, if so, (2) whether the magnitude of improvement can be predicted from individual differences in place-pitch sensitivity. A secondary goal was to determine whether Fidelity120 supports higher levels of speech recognition in noise than HiRes. DESIGN: A within-subjects repeated measures design evaluated speech perception performance with Fidelity120 relative to HiRes in 10 adult CI users. Subjects used the novel strategy (either HiRes or Fidelity120) for 8 weeks during the main study; a subset of five subjects used Fidelity120 for 3 additional months following the main study. Speech perception was assessed for the spectral cues related to vowel F1 frequency (Vow F1), vowel F2 frequency (Vow F2) and consonant place of articulation (Con PLC); overall transmitted information for vowels (Vow STIM) and consonants (Con STIM); and sentence recognition in noise. Place-pitch sensitivity was measured for electrode pairs in the apical, middle and basal regions of the implanted array using a psychophysical pitch-ranking task. RESULTS: With one exception, there was no effect of strategy (HiRes vs. Fidelity120) on the speech measures tested, either during the main study (n=10) or after extended use of Fidelity120 (n=5). The exception was a small but significant advantage for HiRes over Fidelity120 for the Con STIM measure during the main study. Examination of individual subjects' data revealed that 3 of 10 subjects demonstrated improved perception of one or more spectral cues with Fidelity120 relative to HiRes after 8 weeks or longer experience with Fidelity120. Another 3 subjects exhibited initial decrements in spectral cue perception with Fidelity120 at the 8 week time point; however, evidence from one subject suggested that such decrements may resolve with additional experience. Place-pitch thresholds were inversely related to improvements in Vow F2 perception with Fidelity120 relative to HiRes. However, no relationship was observed between place-pitch thresholds and the other spectral measures (Vow F1 or Con PLC). CONCLUSIONS: Findings suggest that Fidelity120 supports small improvements in the perception of spectral speech cues in some Advanced Bionics CI users; however, many users show no clear benefit. Benefits are more likely to occur for vowel spectral cues (related to F1 and F2 frequency) than for consonant spectral cues (related to place of articulation). There was an inconsistent relationship between place-pitch sensitivity and improvements in spectral cue perception with Fidelity120 relative to HiRes. This may partly reflect the small number of sites at which place-pitch thresholds were measured. Contrary to some previous reports, there was no clear evidence that Fidelity120 supports improved sentence recognition in noise.